Impact of connected health interventions on psychological wellbeing and quality of life in patients with cancer: A systematic review and meta‐analysis. Issue 10 (22nd September 2022) - Gitonga, Isaiah; Desmond, Deirdre; Duda, Natalia; Maguire, Rebecca
Abstract: Objective: Connected health technologies have the potential to improve access to cancer care and support and reduce costs. We aimed to assess the impacts of interventions delivered using connected health technologies on psychological and quality of life (QoL) outcomes in people living with and beyond cancer. Methods: PUBMED, PsycINFO, Web of Science, and EMBASE were searched using terms relating to (i) cancer, (ii) connected health, and (iii) QoL/psychological wellbeing. Studies were included if they evaluated interventions using connected health technologies and assessed psychological and/or QoL outcomes for adults at any stage of cancer treatment or survivorship. Results: Thirty‐seven studies met the inclusion criteria with a total of 8956 participants. Connected health technologies included web‐based applications ( n  = 24), smart applications ( n  = 12), and wearable devices ( n  = 1). Studies were heterogeneous in terms of intervention components. We identified five clusters: (i) Psychosocial support and rehabilitation, (ii) psychoeducation and information support, (iii) symptom monitoring, reporting and self‐management, (iv) peer and social support, and (v) health coaching and physical activity training. Due to heterogeneity of outcome measures, the meta‐analysis included only seven RCTs; pooled mean estimates showed connected health interventions were moderately effective in reducing symptoms of depression (SMD: −0.226, 95% CI −0.303/−0.149) and anxiety (SMD: −0.188, 95% CI: 0.279/−0.0963) compared with usual care. Conclusion: While the considerable heterogeneity observed highlights the need for more rigorous studies to improve reproducibility and efficiency, results suggest that connected health interventions have the potential to improve psychological wellbeing and QoL outcomes in people living with and beyond cancer.